Analisis Kerusakan Bantalan Gelinding Pada Sistem Variable Speed Dengan Menggunakan Spektrum Getaran - ariyanto ariyanto (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
The measurement of the overall vibration value on the variable speed transmission system of the knee type milling machine has entered the damaged condition area and further action needs to be taken. More specific measurements are made by observing the frequency of the vibration produced and compared with the theoretical frequency of the component, this method can estimate the component that has decreased ability to damage. Based on the data from the previous history, there was damage to the 3304 bearing. To determine whether the damage to the 3304 bearing was repeated, vibration measurements were made at the observed component frequency. The observed frequencies were Ball Pass Frequency Inner (BPFI), Ball Pass Frequency Outer (BPFO), Fundamental Train Frequency (FTF) and rolling elements/ Ball Spin Frequency (BSF). Observations were made using Vibroport 80 and Report and Examiner. The results of data processing are obtained measuring frequency values that coincide with the calculated frequency values of BSF and BPFI, this indicates damage has occurred in the bearings. Corrective action in the form of replacing damaged bearings with new similar bearings, followed by measuring the overall vibration of the transmission system to see the level of vibration that occurs and referring to the applicable standards